2020
DOI: 10.1186/s40168-020-0792-5
|View full text |Cite
|
Sign up to set email alerts
|

Fecal microbiota transplantation to maintain remission in Crohn’s disease: a pilot randomized controlled study

Abstract: Background: The role of the gut microbiota in Crohn's disease (CD) is established and fecal microbiota transplantation (FMT) is an attractive therapeutic strategy. No randomized controlled clinical trial results are available. We performed a randomized, single-blind, sham-controlled pilot trial of FMT in adults with colonic or ileocolonic CD. Method: Patients enrolled while in flare received oral corticosteroid. Once in clinical remission, patients were randomized to receive either FMT or sham transplantation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
236
1
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(247 citation statements)
references
References 30 publications
4
236
1
6
Order By: Relevance
“…The list of the 60 included references is provided in the Supplemental Digital Content (S1 Table). The 36 records included in the quantitative synthesis comprised all the quasi-experimental studies and RCTs [45][46][47][48][49][50][51][52][53]. Data on these studies are provided in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The list of the 60 included references is provided in the Supplemental Digital Content (S1 Table). The 36 records included in the quantitative synthesis comprised all the quasi-experimental studies and RCTs [45][46][47][48][49][50][51][52][53]. Data on these studies are provided in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…For UC, the results from two randomized trials showed that FMT was more effective than placebo control [61,62], but another randomized trial did not show any significant difference between FMT versus control [63]. For Crohn's disease, FMT resulted in clinical improvement in a pilot study that enrolled pediatric patients and a small separate cohort of adults [64], whereas another randomized, single-blind pilot study showed that FMT did not result in clinical improvement but could serve as a maintenance treatment after corticosteroids [65]. Overall, the clinical evidence for the efficacy of FMT in the treatment of IBD is inconclusive, and another randomized clinical trial is ongoing (https://clinicaltrials.gov/ct2/show/NCT03078803).…”
Section: Discussionmentioning
confidence: 99%
“…Crohn's Disease Endoscopic Index of Severity decreased at 6 weeks in the FMT group (p = 0.03) but not in the control group (p = 0.8). On the contrary, the CRP level increased at 6 weeks in the control group (p = 0.008) but not in the FMT group (p = 0.5) (Sokol et al, 2020). Xiang et al (2020) believed that FMT in CD against targeted therapeutics was efficient, especially hematochezia, abdominal pain, diarrhoea and fever.…”
Section: Crohn's Diseasementioning
confidence: 98%
“…The evidence on the effect of FMT in CD has recently been presented. There are currently several active trials studying the effectiveness of FMT for CD, and the results are diverse ( Table 2) (Cui et al, 2015;Suskind et al, 2015;Wei et al, 2015;Vaughn et al, 2016;Vermeire et al, 2016;Goyal et al, 2018;Gutin et al, 2019;Sokol et al, 2020;Xiang et al, 2020). Xiang et al (2020) studied 174 CD patients treated with FMT via Mid-gut including nasojejunal tube, endoscopy and mid-gut TET (except one through colonic TET).…”
Section: Crohn's Diseasementioning
confidence: 99%